2017
DOI: 10.3345/kjp.2017.60.3.55
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of hereditary nephrotic syndrome: a clinical review

Abstract: Advances in podocytology and genetic techniques have expanded our understanding of the pathogenesis of hereditary steroid-resistant nephrotic syndrome (SRNS). In the past 20 years, over 45 genetic mutations have been identified in patients with hereditary SRNS. Genetic mutations on structural and functional molecules in podocytes can lead to serious injury in the podocytes themselves and in adjacent structures, causing sclerotic lesions such as focal segmental glomerulosclerosis or diffuse mesangial sclerosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…Genetic manipulation of RPCs ex vivo may present an in key podocyte ultrastructure and attachment proteins such as nephrin, podocin, and laminin β2 lead to podocyte dysfunction (Lovric, Ashraf, Tan, & Hildebrandt, 2016) and kidney failure. These patients often fail to respond to frontline steroid therapy, and 50% develop end-stage kidney failure within 15 years (Ha, 2017). While autologous transfer of uRPCs may present an attractive strategy to restore podocyte number, the same genetic mutations would prevent differentiation into functional podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic manipulation of RPCs ex vivo may present an in key podocyte ultrastructure and attachment proteins such as nephrin, podocin, and laminin β2 lead to podocyte dysfunction (Lovric, Ashraf, Tan, & Hildebrandt, 2016) and kidney failure. These patients often fail to respond to frontline steroid therapy, and 50% develop end-stage kidney failure within 15 years (Ha, 2017). While autologous transfer of uRPCs may present an attractive strategy to restore podocyte number, the same genetic mutations would prevent differentiation into functional podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, a number of disease-causing genes have been discovered. To date, about 53 genes are known to cause SRNS and/or FSGS with all types of modes of inheritance [8]. According to its symptoms, SRNS can be isolated or syndromic, and the following 28 genes are known to cause isolated nephrotic syndrome [3,8,12,13] : ADCK4, ARHGDIA, CD2AP, CFH, COQ2, COQ6, CUBN, DGKE, ITGA3, ITGB4, LAMB2, MEFV, MYO1E, NPHS1, NPHS2, PDSS2, PLCE1, PTPRO, SCARB2, SMARCAL1, TTC21B, ACTN4, ARHGAP24, INF2, LMX1B, PAX2, TRPC6, and WT1.…”
Section: Genes Known To Cause Srnsmentioning
confidence: 99%
“…Recent discoveries of genes encoding proteins crucial for the establishment and maintenance of glomerular filtration barrier have revealed the importance of glomerular epithelial cells (podocytes) in the pathogenesis of SRNS [7]. The most common histology of SRNS is focal segmental glomerular sclerosis (FSGS) [8]. About 11-50% of patients with FSGS are at risk of recurrence after kidney transplantation and eventually progress to terminal renal failure [8,9], but the risk for recurrence is lower in FSGS patients with monogenic (single gene) forms of SRNS than those with nonhereditary forms [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although nonhereditary forms of SRNS seem to be prevalent, studies over the last years have identified over 50 dominant or recessive single-gene mutations in a significant percentage (30%) of patients with early-onset SRNS and FSGS (reviewed or discussed in 6,[8][9][10][11] ). While some of these genes have podocyte-specific or -restricted functions, these studies also unveiled the implication of multiple cellular processes in the establishment or maintenance of the glomerular filtration barrier 7,12,13 . In particular, these genetic studies have identified mutations in Nup93 and Nup205, two constituents of the inner ring of the NPC 14 and in Nup107, a constituent of the Y-complex (Nup107/160-complex) that builds up the cytoplasmic and nuclear rings of the NPC 15,16,17 .…”
Section: Introductionmentioning
confidence: 99%